AGROCLIMATIC ZONING FOR EUCALYPTUS IN THE STATE OF PARANÁ AND THE NEW SCENARIOS DEFINED BY GLOBAL CLIMATE CHANGE - Wrege, Marcos Silveira; Caramori, Paulo Henrique; Fritzsons, Elenice; Partala, Adriane; Christensen, Georgia Luize (Revista Geama, 2017)
<span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="EN-US">Brazil is a country with one the largest areas of forest plantations in the world. The state of Paraná (PR) is in the first of three places of designated plantations areas in the country. The main cultivated species are the genus Eucalyptus. In this work, the areas of better favorability for planting the main species of commercial value eucalyptus were defined. Additionally, changes may also occur in these zones in the coming decades, due to global climate change. For this purpose, future scenarios were elaborated, using stochastic tie series simulation software, verifying the possible changes of the climate and indicating potential consequences regarding the changes of eucalyptus plantation zones. The results show that there will be an increase in areas favorable to the commercial plantations of E. grandis and E. urograndis, species cultivated in Cfa climate (subtropical zones). For E. benthamii, a species cultivated mostly in the Cfb (temperate zones), there will be a reduction of area for use in commercial plantations in Paraná, with displacement to areas located to the south and at higher altitudes, where edaphic limitations may occur.